2010
DOI: 10.1098/rspb.2010.0575
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Q fever within dairy cattle herds: key parameters inferred using a Bayesian approach

Abstract: Q fever is a worldwide zoonosis caused by Coxiella burnetii. Although ruminants are recognized as the most important source of human infection, no previous studies have focused on assessing the characteristics of the bacterial spread within a cattle herd and no epidemic model has been proposed in this context. We assess the key epidemiological parameters from field data in a Bayesian framework that takes into account the available knowledge, missing data and the uncertainty of the observation process owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…According to other authors, C. burnetii seropositivity is a risk factor for bacterial shedding (Courcoul et al, 2010). Moreover, consistent with our findings, seroconversion is not observed in non-vaccinated animals (Böttcher et al, 2011;Nogareda et al, 2012) reflecting the high stability of C. burnetii antibodies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to other authors, C. burnetii seropositivity is a risk factor for bacterial shedding (Courcoul et al, 2010). Moreover, consistent with our findings, seroconversion is not observed in non-vaccinated animals (Böttcher et al, 2011;Nogareda et al, 2012) reflecting the high stability of C. burnetii antibodies.…”
Section: Discussionsupporting
confidence: 81%
“…This validated test (García-Pérez et al, 2009) was performed according to the manufacturer's instructions. The sensitivity and specificity of ELISA are 85% and 95%, respectively (Courcoul et al, 2010). The antigen for the ELISA CoxLS kit was isolated from domestic ruminants by INRA in Nouzilly (France).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Table with definitions of the epidemiological model parameters and their values used for simulations [13,24,25]. …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In contrast, several studies have identified parity (McCaughey et al, 2010;Böttcher et al, 2011;Paul et al, 2012;Tutusaus et al, 2013), C. burnetii shedding (Guatteo et al, 2007;Courcoul et al, 2010) and vaccination against the bacterium as maternal factors related to the C. burnetii seropositivity of their offspring. The lack of effects of these factors observed here may be explained by our small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…A sample was scored positive when the S/P ratio > 0.4. The sensitivity and specificity of this ELISA test have been estimated to be 85% and 95%, respectively (Courcoul et al, 2010).…”
Section: Laboratory Testsmentioning
confidence: 99%